2020
DOI: 10.3390/ijms21072327
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channels as Novel Therapeutic Targets for Ovarian Cancer Stem Cells

Abstract: Drug resistance in epithelial ovarian cancer (EOC) is reportedly attributed to the existence of cancer stem cells (CSC), because in most cancers, CSCs still remain after chemotherapy. To overcome this limitation, novel therapeutic strategies are required to prevent cancer recurrence and chemotherapy-resistant cancers by targeting cancer stem cells (CSCs). We screened an FDA-approved compound library and found four voltage-gated calcium channel blockers (manidipine, lacidipine, benidipine, and lomerizine) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…Compared with their parental EOC cell lines, A2780-SP and SKOV3-SP cells exhibited CSC characteristics. A2780-SP cells have higher messenger RNA (mRNA) and protein levels of stemness markers than A2780 cells [ 15 , 22 ], and SKOV3-SP cells expressed higher mRNA levels of stemness markers than SKOV3 cells ( Figure S1A ). In addition, A2780-SP cells expressed higher mRNA levels of ERBB4 (HER4) [ 16 ], and SKOV3-SP cells expressed higher mRNA levels of ERBB2 (HER2) and ERBB4 (HER4) than their parent cells ( Figure S1B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with their parental EOC cell lines, A2780-SP and SKOV3-SP cells exhibited CSC characteristics. A2780-SP cells have higher messenger RNA (mRNA) and protein levels of stemness markers than A2780 cells [ 15 , 22 ], and SKOV3-SP cells expressed higher mRNA levels of stemness markers than SKOV3 cells ( Figure S1A ). In addition, A2780-SP cells expressed higher mRNA levels of ERBB4 (HER4) [ 16 ], and SKOV3-SP cells expressed higher mRNA levels of ERBB2 (HER2) and ERBB4 (HER4) than their parent cells ( Figure S1B ).…”
Section: Resultsmentioning
confidence: 99%
“…AKT is phosphorylated downstream of PI3K signaling [ 32 , 33 ], and ERK phosphorylation is enhanced by overexpression of the ErbB4 receptor [ 16 , 34 ]. The overexpressed L/T-type calcium channels increase calcium flow into the cytoplasm, which drives phosphorylation of AKT and ERK through PI3K and MAPK signaling [ 15 , 35 ]. The phosphorylation of AKT and ERK stabilizes β-catenin, which translocates into the nucleus from the cytoplasm to increase transcription of CD133, NANOG, SOX2, and KLF4, thereby maintaining the stemness of ovarian CSCs ( Figure 5 D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1984, Tsuruo et al ( Tsuruo, 1984 ) found that calcium regulators might increase the level of anti-tumor cells and reduce anti-tumor resistance by inhibiting the delivery of anti-tumor drugs from cancer cells. Recent studies have shown that CCBs reduce the ball formation, viability and proliferation of ovarian cancer stem cells (CSCs), and induce their apoptosis ( Lee et al, 2020 ). Moreover, recent studies have also suggested that the traditional diuretic spironolactone might increase the death and inhibit cell growth of cancer cells treated with gemcitabine and osimertinibe mainly by regulating the expression of the anti-apoptotic protein surviving ( Sanomachi et al, 2019 ).…”
Section: Anti-hypertensive Drugs Affect Cancer Progression Through Mumentioning
confidence: 99%
“…On a similar note, Lee et al have tested four FDA-approved calcium channel blockers targeting ovarian cancer stem cells (CSCs). They found that these compounds not only decreased the expression of the antiapoptotic factors survivin, B-cell lymphoma 2 (Bcl-2), and myeloid cell leukemia 1 (Mcl-1), but also induced caspase activation, highlighting their potential use as anticancer agents [ 100 ].…”
Section: Intracellular Calcium Regulation In Ovarian Physiology Anmentioning
confidence: 99%